Pengembangan Model Analisis Standar Belanja (ASB) Kota Malang - susenohaji susenohaji (Program Pendidikan Vokasi Universitas Brawijaya, 2018)
The aim of this study was to analyze the Standard of Spending Model Development in Malang City. The standard is determining the fairness and accountability of budget allocation model to each local government unit. This study developed previous model of Spending Standard Analysis for the program of the so-called BIMTEK or “Bimbingan Teknis”(a kind of technical guidance activity to help practicioners in dealing with Spending Standard Analysis) from the single model to multiple model. Single model was affected to the unfairness of budget allocation. Data sample were take from 2010 until 2016 which consists of 210 panel data from the Budget Allocation Document (DPA) from 15 local governmental units.The writer identified and divided 4 models based on BIMTEK activity characteristics and expenses account. There are two characteristics activity variables as the model determination, such as activity place (impact to rent expense) and official duties. These activity characteristics have impact on the amount of budget allocation for each BIMTEK. Then, the writer identified and determined the fixed and variable cost for each model. Cost Driver was built to allocation of variable expenses. The data were analyzed by using Simple Linear Regression to determine amount of fixed cost and variabel cost for each model. Finally, four models of Standard Spending Analysis in Malang City have been created and are expected to be able to create the fairness and accountability of budget allocation.